2005
DOI: 10.1002/ajmg.a.30835
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of a de novo supernumerary ring chromosome 7 resulting in partial trisomy, tetrasomy, and hexasomy in a child with dysmorphic signs, congenital heart defect, and developmental delay

Abstract: We report on a girl with mosaicism (65%) of a de novo supernumerary ring chromosome 7. The main clinical features were delayed psychomotor development, congenital heart defect, facial dysmorphisms, and long hands, fingers, feet and toes. Molecular cytogenetic analysis revealed that the ring chromosome was duplicated in 20% of the analyzed metaphases with marker chromosome and quadruplicated in 5% thereof. Uniparental disomy (UPD) of the two normal sister chromosomes 7 was excluded. This is, to our knowledge, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Monosomy 7, one complete ring, supernumerary large rings, and duplicated rings of chromosome 7, were detected. Most previous reported cases of supernumerary ring chromosome 7 showed a majority of cells with a normal karyotype, in addition to some cells with a partial trisomy containing small rings [20-26]. Here we present a newborn girl that survived with a mosaic karyotype with a complete supernumerary ring chromosome 7 and a few monosomy 7 cells, without any cell with normal karyotype detected in peripheral lymphocytes.…”
Section: Discussionmentioning
confidence: 73%
“…Monosomy 7, one complete ring, supernumerary large rings, and duplicated rings of chromosome 7, were detected. Most previous reported cases of supernumerary ring chromosome 7 showed a majority of cells with a normal karyotype, in addition to some cells with a partial trisomy containing small rings [20-26]. Here we present a newborn girl that survived with a mosaic karyotype with a complete supernumerary ring chromosome 7 and a few monosomy 7 cells, without any cell with normal karyotype detected in peripheral lymphocytes.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, one fetus with chromosome 7 tetrasomy (48,XN,+7,+7) was found in this study. Study has shown that partial tetrasomy of chromosome 7 can cause dysmorphic signs, congenital heart defect, and developmental delay (von Beust et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…4). The boy was able to correctly pronounce only a very small number of words, but scored at a much higher ability level on receptive vocabulary and on nonlanguage tasks.Individuals with larger chromosome 7 duplications that include 7q11.23 also present with speech and language impairment, along with mild developmental delay (Refs 72,86,87,88,89,90,91). A review of these reported patients also suggests the presence of a subtle but recognisable facial phenotype, consisting of a high broad nose, posteriorly rotated ears, high arched palate and short philtrum.…”
mentioning
confidence: 99%